The strategy for developing the Kalipucang dairy farming agribusiness area as a dairy village agroedutourism using the business model canvas - Dayat, M; Soetjipto, Budi Eko; Wardoyo, Cipto (AGROMIX, 2024)
Introduction: Efforts to enhance the agribusiness sector, particularly in dairy farming, require integrated development alongside other local potentials. This study aims to establish a model for dairy cattle agribusiness development integrated with the village's superior potential, utilizing the Business Model Canvas (BMC). Methods: The research involved mapping the dairy cattle agribusiness in Kalipucang Tutur Pasuruan Village using the BMC framework. The study analyzed the fulfillment of the nine BMC element blocks and identified strategies for enhancing productivity through SWOT analysis. Results: The mapping revealed that the dairy agribusiness in the village offers animal husbandry educational tours and satisfies the BMC element blocks. However, there is a need for strategic enhancements to boost productivity. The strategic analysis also identified the potential for developing agroedutourism due to the advantageous location near tourist spots. Conclusion: The integration of dairy cattle agribusiness with local potentials, as outlined in the BMC mapping, presents opportunities for further development. Strategic recommendations derived from the SWOT analysis provide insights for optimizing productivity and leveraging the area's potential for agroedutourism.